PENGETAHUAN REMAJA PUTRI TENTANG SADARI TAHUN 2022 - Desri Nova Hamid; Oktaliza Elektrina (Maternal Child Health Care, 2023)
Global Cancer Observatory data from the World Health Organization (WHO) said that there were around 58,256 cases of breast cancer or 16.7% of a total of 348,809 cases or 16.7% of a total of 348,809 cancer cases. And in 2019 it is predicted that 9 million people will die from cancer and increase to 13 million people per year in 2030. The purpose of this study is to find out the knowledge of young women about realizing at SMK Prima Nusantara Bukittinggi in 2022. This research is a quantitative study where the population in This study included all female students at SMK Prima Nusantara with a total population of 75. The sampling technique was total sampling and univariate analysis was carried out. The results of the study were obtained from 75 respondents, the knowledge of young women about how to be conscious was lacking as many as 32 respondents (43%), the procedure was less aware, as many as 32 respondents (43%), knowledge about when conscious was moderate, as many as 31 respondents (41%) and knowledge about the results of the examination aware of the less knowledgeable respondents as many as 40 respondents (53%), it is expected for SMK Prima Nusantara Bukittinggi. It is hoped that the school can always provide health promotion about the importance of knowing breast self-examination (aware).